Α-Aminoisobutyric acid incorporation induces cell permeability and antiviral activity of HIV-1 major homology region fragments1. Issue 62 (11th August 2015) - Lampel, Ayala; Elis, Efrat; Guterman, Tom; Shapira, Sharon; Marco, Pini; Bacharach, Eran; Gazit, Ehud
<x xml:space="preserve">Abstract</x> A cell-penetrating peptide derived from HIV-1 major homology region, incorporating the non-coded α-aminoisobutyric acid, inhibits viral assembly and infectivity.